Effectiveness of New Product Development on Mat Creative Industry - Eko Prasetyo, P; ., Rusdarti; Aulia Rahman, Y (KnE Social Sciences, 2018)
In the very competitive era, the industrial companies are forced to launch the efficient, effective, and adaptive new products. This research aims at analyzing the strategy and the level of effectiveness of developing the new products on the mat creative industry in Semarang Regency. The main data source used is the primary data using the Ansoff Matrix analysis model and especially the index value of effectiveness of product development (NPI, FFI, MTMI and RDSI). Besides, it also uses the index value of selling effectiveness, costumer and supplier responsive, and the operational efficiency index. The result of research indicates that all strategies of Ansoff growth have significantly contributed in increasing the profitability performance of mat industry and there is a tendency to frequently conduct the partial product diversification on the market expansion level. Besides, the ability of modifying the new product development is getting higher, more competitive and responsive to the market, so that the effectiveness of industry is getting better and more adaptive and the cash operational tends to be more efficient. However, the effectiveness level of ability in developing the new products is generally still low and not adaptive yet so that the level of productivity and competitiveness of the mat industry is still low. Keywords: effectiveness, strategy, new product development, adaptive and efficient